A Coupled Lagrangian-Earth System Model for Predicting Oil Photooxidation - Vaz, Ana C.; Faillettaz, Robin; Paris, Claire B. (Frontiers in Marine Science, 2021)
During the Deepwater Horizon (DWH) blowout, photooxidation of surface oil led to the formation of persistent photooxidized compounds, still found in shoreline sediments a decade later. Studies demonstrated that photooxidation modified both biodegradation rates of the surface oil and the effectiveness of aerial dispersant applications. Despite the significant consequences of this weathering pathway, the lack of measurements prevented photooxidation to be accounted for in the DWH oil budget calculations and in most predictive models. Here we develop a Lagrangian photooxidation module that estimates the dose of solar radiation individual oil droplets receive while moving in the ocean, quantifies the likelihood of photooxidative changes, and continues to track the transport of these persistent photooxidized compounds. We estimate and track the likelihood of photooxidation of Lagrangian oil droplets in the upper layers of the water column for the DWH case by coupling the net shortwave radiation from NOGAPS to the oil application of the Connectivity Modeling System (oil-CMS). The dose of solar radiation upon a droplet is computed with the intensity of the incoming irradiance at the ocean’s surface, the light attenuation coefficient, and the depth of the oil droplets. Considering a range of DWH empirical irradiance thresholds, we find that photooxidation can happen at short time scales of hours to days, in agreement with the new paradigm of oil photooxidation. Furthermore, the oxidized compounds are likely to form in a 110 km radius around the response site, suggesting that the oil reaching the coastline was already photooxidized. This new dynamic coupling provides a powerful tool to test oil weathering hypotheses, refine the oil budget during the DWH, and ultimately inform rapid response in future oil spills.